Etymology and Word Decoding - Baghdasaryan, Susanna (Armenian Folia Anglistika, 2009)
The language vocabulary is a system which grows mostly due to word formation. The latter takes place with the help of own or borrowed parts of words (root and suffix), which, certainly, used to be independent words. They penetrated the English vocabulary and made up new words while preserving their previous meanings. Most of the Latin and Greek borrowings do not make up the active vocabulary. They usually refer to scientific terms.